2022
DOI: 10.2490/prm.20220007
|View full text |Cite
|
Sign up to set email alerts
|

Interferential Current Stimulation for Swallowing Disorders in Chronic Obstructive Pulmonary Disease: A Preliminary Study

Abstract: Swallowing function is affected in patients with chronic obstructive pulmonary disease (COPD), putting them at risk of exacerbation of COPD. We previously reported the effectiveness of the repetitive saliva swallowing test (RSST) in screening for patients at risk of COPD exacerbation. However, evidence on how to improve swallowing function in this population is extremely limited. Interferential current transcutaneous electrical sensory stimulation (IFC-TESS) stimulates the larynx and pharynx, thereby improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The limitations of this study are that although patients' swallowing function was evaluated by VFSS and endoscopy, the outcome measure was only FILS, which is an observational tool to assess nutritional status, and it was a retrospective study. All studies in the literature on the treatment of dysphagia with IFC stimulation have used Gentle Stim® (J Craft, Osaka, Japan), a portable device approved for use in Japan [13][14][15][16][17][18]22,23,26,[31][32][33]. As in this study, we believe that an alternative device capable of providing IFC stimulation can also be used for treatment.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The limitations of this study are that although patients' swallowing function was evaluated by VFSS and endoscopy, the outcome measure was only FILS, which is an observational tool to assess nutritional status, and it was a retrospective study. All studies in the literature on the treatment of dysphagia with IFC stimulation have used Gentle Stim® (J Craft, Osaka, Japan), a portable device approved for use in Japan [13][14][15][16][17][18]22,23,26,[31][32][33]. As in this study, we believe that an alternative device capable of providing IFC stimulation can also be used for treatment.…”
Section: Discussionmentioning
confidence: 80%
“…Based on these results, IFC stimulation may contribute to the prevention of aspiration pneumonia [13][14][15]. Other studies have reported that IFC stimulation can reduce dysphagia and chronic obstructive pulmonary disease (COPD) exacerbations in COPD patients with dysphagia [23,31]. It has also been reported that IFC stimulation can increase salivation in people with dry mouth without causing pain or physical distress [33].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A incoordenação entre a respiração e deglutição reduz a proteção de vias aéreas superiores, aumentando o risco de aspiração laringotraqueal (Yoshimatsu, 2020;Prestes et al, 2020). Estudos demonstram uma relação entre disfagia e agravamento da DPOC (Yoshimatsu, 2020;Favero;Texeira;Cardoso, 2020;Yoshimatsu et al, 2022). A detecção precoce de alterações na deglutição na fase inicial da DPOC é crucial para prevenir estágios avançados da doença e gerenciar esses pacientes (Ohta et al, 2009).…”
Section: Introductionunclassified